Pride, mindfulness, public self-awareness, affective satisfaction, and customer citizenship behaviour among green restaurant customers. (October 2019) - Hwang, Kumju; Lee, Bora
Highlights: Green restaurant customers' pride was positively associated with their public self-awareness. Green restaurant customers' mindfulness was positively associated with their public self-awareness. Green restaurant customers' pubic self-awareness was positively associated with their affective satisfaction. Green restaurant customers' public self-awareness is positively associated with their customer citizenship behavior (CCB). The finding indicates that green restaurant customers' affective satisfaction is positively associated with CCB. Abstract: Although research on the self has a long history with various psychological perspectives, the role of the self in visiting green restaurants has not been sufficiently explored. This study investigated the influence of public self-awareness (PSA) as a mechanism of the motivation for green restaurant consumption on customers' satisfaction and customer citizenship behaviour (CCB). Additionally, this study examined customers' pride and mindfulness as antecedents of their PSA. A survey of 341 regular customers of green restaurants was conducted, and the partial least square method was used to analyse the data. The findings indicated a positive association between pride and PSA, as well as between mindfulness and PSA. Furthermore, PSA influenced affective satisfaction and CCB, and affective satisfaction had a positive impact on CCB. The theoretical and practical implications of the findings are discussed.